Uganda : Technical Assistance Report-Monetary and Foreign Exchange Operations, Recapitalization, and Act Revision. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2018)
This Technical Assistance Report discusses the findings and recommendations made by the IMF mission regarding monetary and foreign exchange operations in Uganda, Bank of Uganda (BOU) recapitalization, and Bank of Uganda Act revision. The presence of sizable precautionary and involuntary reserves and excessive short-end volatility has weakened the transmission mechanism in Uganda. The key challenge remains to enhance monetary and fiscal policy coordination and to ensure that institutional and operational arrangements are robust and conducive to efficient monetary operations framework. The BOU should raise the effectiveness of the monetary and foreign exchange operations framework. To foster further market development there is need to anchor short-term interest rates by using various fine-tuning instruments to ensure improved operational efficiency and strengthen transmission of policy signals across the curve.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet